Paralogs and Off-Target Sequences Improve Phylogenetic Resolution in a Densely SampledStudy of the Breadfruit Genus (Artocarpus, Moraceae) - Gardner, Elliot M; Johnson, Matthew G; Pereira, Joan T.; Aida Shafreena, Ahmad Puad; Deby, Arifiani; Sahromi, .; Wickett, Norman J; Zerega, Nyree J C (Oxford University Press, 2020)
We present a 517-gene phylogenetic framework for the breadfruit genusArtocarpus(ca. 70 spp., Moraceae), makinguse of silica-dried leaves from recent fieldwork and herbarium specimens (some up to 106 years old) to achieve 96% taxonsampling. We explore issues relating to assembly, paralogous loci, partitions, and analysis method to reconstruct a phylogenythat is robust to variation in data and available tools. Although codon partitioning did not result in any substantial topologicaldifferences, the inclusion of flanking noncoding sequence in analyses significantly increased the resolution of gene trees. Wealso found that increasing the size of data sets increased convergence between analysis methods but did not reduce gene-tree conflict. We optimized the HybPiper targeted-enrichment sequence assembly pipeline for short sequences derived fromdegraded DNA extracted from museum specimens. Although the subgenera ofArtocarpuswere monophyletic, revision isrequired at finer scales, particularly with respect to widespread species. We expect our results to provide a basis for furtherstudies inArtocarpusand provide guidelines for future analyses of data sets based on target enrichment data, particularlythose using sequences from both fresh and museum material, counseling careful attention to the potential of off-targetsequences to improve resolution. [Artocarpus; Moraceae; noncoding sequences; phylogenomics; target enrichment.]